Strategi Forum Kordinasi Pencegahan Terorisme (FKPT) Provinsi Papua Dalam Menanggulangi Paham Radikalisme - Untung Mhdiarta; Muliadi Anangkota; Diego Romario De Fretes (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2025)
The designation of Armed Criminal Groups as terrorists invites pros and cons, because some believe that implementing this status could lead to increased violence in Papua and innocent civilians could be affected, so the government is asked to take another approach. Separatist movements that develop into terrorists, however, cannot be justified because they can threaten the sovereignty and integrity of the Unitary State of the Republic of Indonesia. The implementation of the status of the Free Papua Organization as an Armed Criminal Group and then a terrorist is not without basis. This research is descriptive qualitative research, a type of research with the aim of describing phenomena or dynamics that occur using data collection methods in the form of interviews and observations. FKPT in carrying out counter-radicalism outreach certainly has big obstacles. Radicalism is difficult to detect because it is a latent danger that exists but is not visible. As long as there are still many in our society who don't know what radicalism is, they only have passionate religious zeal but lack sound and social reasoning, so during that time they will be indoctrinated by groups that are indicated by this radicalism. Apart from that, the obstacles faced by FKPT Papua not only occur outside the FKPT itself, but also within the FKPT internally. This can be seen from the top down way of working of FKPT Papua. Because the funding comes directly from BNPT, the only activities carried out are those determined by the Central BNPT. Thus, this means that the abilities of the FKPT management are not channeled properly in preventing counter-radicalism